Implementasi Strategi Point-Counterpoint untuk Meningkatkan Keterampilan Berbicara Mata Pelajaran Bahasa Indonesia pada SiswaKelas VI SD Negeri Karangasem I Tanon Sragen Tahun Ajaran 2014/2015 - Kunardi, Enggar Putri; , Dra. Risminawati, M.Pd (2015)
This research aims to improve the skills of speaking students on the subjects of the Indonesian Language class VI in SD Negeri Karangasem I Tanon Sragen with the application of the Point-Counterpoint strategy. A kind of this research is research the act of class (PTK). The subject of this research is teachers (researchers) and students class VI of SD Negeri Karangasem I Tanon Sragen which amounted to 23 students consisting of 20 son and daughter 3. Data collection techniques using observation, interviews and documentation. While the technique of analysis of data used in this research in an interactive analysis model consisting of the reduction of data, exposure to the data and the withdrawal of conclusion. Based on the results of research shows an improvement in skill talk students class VI in SD Negeri Karangasem I Tanon. The increase in the skills of speaking is evident from the data obtained the results of skill is increasing talk of pre cycle of 39,13%, I cycle of 52,17% and II of cycle 82,61%. The conclusion of this research that the implementation of strategies can improve Point-Counterpoint speaking skills students on the subjects Indonesian Language of SD Negeri Karangasem I Tanon Sragen Academic Year 2014/ 2015.